The influence of teaching variables in the educational processes of students with rare diseases - García-Perales, Ramón; Palomares-Ruiz, Ascensión; García-Toledano, Eduardo; Martín-García, María Inés (Frontiers in Psychology, 2023)
Introduction Teachers have a key role in their students’ educational inclusion processes. Numerous variables influence their professional work and determine how they approach teaching. Methods In this study, 574 teachers teaching non-university educational stages in the Autonomous Community of Castilla-La Mancha were queried about their knowledge and perceptions regarding students with rare diseases, examining the extent to which there were personal variables that could have an impact on that. Results The results indicate the need to expand training to increase levels of knowledge in the educational arena about rare diseases, especially about how they are conceptually described and their categorization and prevalence. All of the teaching variables evaluated were statistically significant, with p < 0.001 in most of the elements evaluated according to each of the following variables: sex, age, job position, teaching experience, and higher qualifications. This shows that there are teaching variables that influence the inclusion of students with rare diseases. Being aware of them should be a priority in order to increase teacher empowerment for the delivery of inclusive educational processes. Discussion All students exhibit distinctive characteristics and teachers play an essential role in offering them quality individualized education. The full inclusion of all students is something educational systems have yet to achieve, and this study aimed to contribute to that goal, in this case for schoolchildren with rare diseases.